34x+99=3(14x+9)

Simple and best practice solution for 34x+99=3(14x+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 34x+99=3(14x+9) equation:



34x+99=3(14x+9)
We move all terms to the left:
34x+99-(3(14x+9))=0
We calculate terms in parentheses: -(3(14x+9)), so:
3(14x+9)
We multiply parentheses
42x+27
Back to the equation:
-(42x+27)
We get rid of parentheses
34x-42x-27+99=0
We add all the numbers together, and all the variables
-8x+72=0
We move all terms containing x to the left, all other terms to the right
-8x=-72
x=-72/-8
x=+9

See similar equations:

| 3k+5k-6=8k+3-9 | | 3.2x+0.5(7.3-x)=4.7-6.4(×-2.1) | | 9a+8=44 | | 7.5/n=33.75 | | 2/5(25b)-40=1/4(16b+8 | | -3(2x-5)+2=-4x-3 | | 2/3p=3/5 | | 11=5-2p-p | | 7/6=1/12d | | 6-c=-18 | | x-12=8.3 | | 1-8x+4x=9 | | 2x+5=3(x+1)-5 | | 5(y-7)-3=3(y+4) | | 14y+26=138 | | 3x+6+x+4=x+2+3x6 | | 8=-18+3/8(16-40n | | 2x^-10=x | | 8x+10-4x=2x-20 | | 40=5+7x | | 36x^-4-13x^-2+1=0 | | 4(2r+4)=3/4(24-8r) | | 25x+4=27x | | 99=-7d+8 | | 39=6r-3 | | 1/3(9x-12)=3x+3 | | .25x+7=2 | | 7x-15=16.5 | | Y=-1/4x+8 | | 1.1x+1.2x−5.4=−10x= | | -7(x+)+2=3 | | 10x+2=32x= |

Equations solver categories